The foxes that ruin the vineyards - a literal interpretation of Song of Songs 2:15 - S. Fischer (Acta Theologica)
This article focuses on a literal interpretation of Song of Songs 2:15. Initially, this verse is identified as an independent unit, as a song intended to scare off. Now it forms part of a garden/countryside scenery (2:8-17). In 2:15 the co-workers of the lover are addressed. They are asked to create an intimate mood by setting the lover free from his work, and to catch the foxes instead of him.